Navigating Growth and Sustainability: Technological Advances, Renewable Energy, and Environmental Quality - Sumaira; Meiling Li; Xie Yun; Yasir Ali; Bibi, Robeena (Journal of Environmental Science and Economics, 2025)
The rise in economic growth driven by increased production and industrialization has led to greater energy demand, which in turn has caused higher carbon emissions and a deterioration in environmental quality. Technological innovations aimed at improving energy efficiency, enhancing production efficiency, and utilizing renewable energy in industrial processes offer potential solutions to address environmental degradation. This study investigates the impact of technological innovations, renewable energy consumption, and economic growth on environmental degradation in OECD countries from 1989 to 2024. Using fixed effects and a two-step generalized method of moments, the findings indicate that economic growth and high technology exports negatively impact environmental quality, while patent applications and R&D efforts significantly reduce emissions. The Innovation Claudia curve is confirmed through the squared term of the innovation indicator, although the innovation index itself is found to have a positive impact on carbon emissions. Notably, the study concludes that increasing the adoption of renewable energy sources leads to substantial improvements in environmental quality. These findings have important implications for the governments of the countries studied.